2007
DOI: 10.1063/1.2784940
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced domain wall depinning and magnetoresistance in La0.7Sr0.3MnO3 planar spin valves

Abstract: The authors have performed experiments on current-induced domain wall (DW) displacement in La0.7Sr0.3MnO3 nanostructures patterned by gallium (Ga) focused-ion-beam milling. A dc current is found to assist or hinder, according to polarity, an external magnetic field in the depinning of a DW trapped in a nanoconstriction. For large enough currents, the DW depinning occurs in the absence of external magnetic field. The depinning current depends on the transverse anisotropy constant of the region toward which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In the past decades many improvements in the fabrication of artificial magnetic nanostructures, 1 thin films, [2][3][4] and superlattices 5,6 have been made, tailoring the properties of a large class of materials exploiting advanced techniques of patterning and stress relaxation mechanisms. For instance, it has been found that the symmetry breaking at atomic steps or anisotropic lattice relaxation are at the origin of an additional inplane uniaxial magnetic anisotropy contribution in epitaxial magnetic thin films with cubic crystal symmetry, firstly observed in metal systems 7 and more recently in diluted semiconductors 8 as well as oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades many improvements in the fabrication of artificial magnetic nanostructures, 1 thin films, [2][3][4] and superlattices 5,6 have been made, tailoring the properties of a large class of materials exploiting advanced techniques of patterning and stress relaxation mechanisms. For instance, it has been found that the symmetry breaking at atomic steps or anisotropic lattice relaxation are at the origin of an additional inplane uniaxial magnetic anisotropy contribution in epitaxial magnetic thin films with cubic crystal symmetry, firstly observed in metal systems 7 and more recently in diluted semiconductors 8 as well as oxides.…”
Section: Introductionmentioning
confidence: 99%
“…18 In particular, the strain in LSMO thin films deposited on SrTiO 3 (STO) (001) is in-plane tensile, and an in-plane biaxial magnetic anisotropy is generally observed, with the easy in-plane direction along 100 h i and the hard in-plane direction along 100 h i. [18][19][20][21][22][23] In the case of LSMO grown onto STO(110), the substrate induces a strain that is anisotropic in-plane (i.e., the two in-plane directions of strain are inequivalent).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their perovskite crystal structure common to other functional oxides such as high-T c superconducting cuprates and ferroelectric titanates, allows the growth of epitaxial heterostructures and realisation of novel devices. A noteworthy potential in this field is related to the recent improvements in nanopatterning techniques, applied to manganites, such as electron beam lithography [3,4], local anodisation by atomic force microscopy (AFM) [5], focused ion beam (FIB) [6][7][8] direct lithography. In particular, FIB patterning is usually performed with two different approaches: one is to remove material by ion milling [9], the other is to change locally the magnetic properties by ion-induced damage at low-dose irradiation, without material erosion.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic properties of half-metallic ferromagnetic La 0.7 Sr 0.3 MnO 3 (LSMO) films are known to be very sensitive to both crystallographic and morphological variations [1][2][3][4]. For (001)-oriented LSMO the strain imposed by the lattice mismatch between the film and the substrate can determine the magnetization easy-axis orientation, i.e., magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%